(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
Science Fiction ( henceforth SF ) has gained special attention as an outstanding literary genre because it is based on science and technology and their vital role in the human societies. It is the fiction that deals with facts rather than myths or mere imagination, and it has indeed, affected these human societies by the feelings it arouses against the numerous achievements of progress in technology and industry. Thus, an investigation of the language of such kind of genre is necessary to reveal its texture. In the present investigation, three grammatical and semantic categories have been selected for this purpose, viz. Tense, Aspect and Modality, since they constitute a very important triple that is attached to the verb, which is in turn, the heart of the sentence. The questions that this study has to answer are: which tense SF writers tend to use more frequently, which aspect is predominant; the perfective or the progressive one, and how modality is treated syntactically and semantically.